2019
DOI: 10.1177/1940082919849504
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Araceae in Young Forests Highlights the Importance of Mature Forest Conservation

Abstract: We compared Araceae abundance among mature forests, secondary forests, and plantations (8-14 years) in central Panama. Araceae colonization was virtually nonexistent in secondary forests and plantations. Low humidity, relatively short forest stature, and time could drive this absence. These results highlight the conservation value of forests containing intact populations of Araceae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Non-collected Araceae can grow wild because the seeds disperse outside the Araceae collection gardens. Barrancos et al (2019) andRenner (2004) reported Araceae could disperse via wind, water current, and animals, such as a bird. Furthermore, Araceae grow in a wide range of environments, so they are easy to find anywhere (Croat, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Non-collected Araceae can grow wild because the seeds disperse outside the Araceae collection gardens. Barrancos et al (2019) andRenner (2004) reported Araceae could disperse via wind, water current, and animals, such as a bird. Furthermore, Araceae grow in a wide range of environments, so they are easy to find anywhere (Croat, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…
Vascular epiphytes are extraordinarily diverse in the tropical Andean region, reaching up to 50% of vascular plant species diversity at a local scale (Gentry and Dodson, 1987a,b). Compared to trees and terrestrial herbs, epiphytes are more vulnerable to forest alteration due to their environmental requirements such as higher humidity and substrate accumulation (Nadkarni, 2000;Köster et al, 2013;Barrancos et al, 2020). Seeds and spores of epiphytes arrive and colonize host trees, increasing species biomass and abundance in a well-establishedFrontiers in Forests and Global Change frontiersin.org
…”
mentioning
confidence: 99%